Meeting the New AACP Competencies in Genetics and Clinical Pharmacogenomics at the University of Minnesota - Jacob Brown; Lindsay A Sorge; William S Oetting; Pamala A Jacobson; Chrystian Pereira (University of Minnesota Libraries Publishing, 2024)
Objective: Pharmacogenomics (PGx) is increasingly being used for creating individualized treatments for patient care. Healthcare professionals, especially pharmacists, need to understand how genetic variation impacts the efficacy and toxicity of medications. Due to the breadth and complexity of PGx-related information, it has been challenging to determine what information should be included in pharmacy curricula and how best to educate students. Methods: The University of Minnesota College of Pharmacy recently began the process of incorporating into the curriculum expanded competencies for PGx from the American Association of Colleges of Pharmacy (AACP) Pharmacogenomics Special Interest Group (PGx-SIG). We evaluated our curriculum for PGx content, determined what was currently being taught and identified educational gaps.  Results: A review of our Doctor of Pharmacy curriculum showed substantial PGx content, although it was inconsistently taught throughout the required courses and in some courses absent. We revised the content of existing courses incorporating content that meet most of the PGx-SIG recommended competencies.  Conclusion: There are and will be major changes in our understanding of the influences of PGx on individualized medical treatment.  As our understanding grows, information on PGx in pharmacy curriculums will need to keep pace with these changes. We have begun this process at the University of Minnesota by doing a full review of PGx related information and making appropriate revisions in the pharmacy curriculum.